Preoperative Chronic Pain as a Risk Factor for Early Postoperative Cognitive Dysfunction in Elderly Patients Undergoing Hip Joint Replacement Surgery: A Prospective Observational Cohort Study - Huai, Xiaorong; Jiao, Yingfu; Gu, Xiyao; Zhu, Huichen; Chen, Lingke; Fan, Yichen; Yu, Weifeng; Su, Diansan; Xie, Hong (Frontiers in Neuroscience, 2021)
Background: Although major joint replacement surgery has a high overall success rate, postoperative cognitive dysfunction (POCD) is a common complication after anesthesia and surgery, increasing morbidity and mortality. Identifying POCD risk factors would be helpful to prevent and decrease the occurrence of POCD. We hypothesized that preoperative chronic pain increases the risk of POCD. Methods: A single-center, observational, prospective cohort study was conducted from January 2018 to March 2020. All consecutive elderly patients (>65 years) who underwent elective total hip arthroplasty or hemiarthroplasty with general anesthesia by the same surgeon were enrolled. The patients underwent neuropsychological testing preoperatively and at 7 days and 2 months after surgery. To determine POCD, a nonsurgical control group was recruited from the general community. Results: Of the 141 patients who finished the neuropsychological testing 7 days after surgery, 61 (43.2%) had preoperative chronic pain. Of the 61 patients, 17 (27.9%) developed POCD; of the 79 patients with no chronic pain, 10 (12.7%) had developed POCD by 7 days after surgery. Multivariate logistic regression analysis identified preoperative chronic pain as a risk factor of POCD assessed 7 days after surgery (odds ratio 6.527; P = 0.009). There was no significant difference in the POCD incidence 2 months after surgery between patients with and without preoperative chronic pain. Conclusion: Preoperative chronic pain was a risk factor of developing POCD within 7 days after surgery in elderly patients following hip joint replacement surgery. Clinical Trial Registration: [www.ClinicalTrials.gov], identifier [NCT03393676].